The management of solid waste at construction site in Kelantan case study: in Kota Bharu and Tanah Merah, Kelantan / Nor Azma Ismail - Ismail, Nor Azma (2010)
Management is important in a construction of housing project. With qualified and efficient management providing, all works in the site project can be carry as schedule. One of the important management aspects in the site is management of construction waste. Research has be done with considered the best important process in wasted management, such as buying, transportation, monitoring, delivering, remaining and wasting of construction material. All information and data that interconnected in this research are collected through the interview with developer and contractor that monitored all project at Kota Bharu and Tanah Merah district in Kelantan. The objective of this research is to investigate the best management method of waste material in the construction site and to identify the problem that occur due to waste material exist on surrounding area of the construction site. According to the survey, most method of disposal of building material is burying at construction site, sent to disposal center, bake at the construction site, take and remove to other places and this is also the foremost important factors that cause major problem at the construction site.